Lytic characterization and application of listerial endolysins PlyP40 and PlyPSA in queso fresco - Maxwell J. Holle; Michael J. Miller (JDS Communications, 2021)
Queso fresco (QF) is a fresh Hispanic-style cheese that is commonly associated with the human foodborne pathogen Listeria monocytogenes and outbreaks of listeriosis in the United States. Endolysins, cell wall hydrolases derived from bacteriophages, are promising candidates for controlling bacterial pathogens in food systems. In this study, we characterized the lytic capabilities of 2 endolysins, PlyP40 and PlyPSA, under varying conditions (pH, temperature, salt concentration) and compared their activities with those of the previously described endolysin PlyP100. We showed that PlyP40 was effective, showing at least a 33% reduction in cellular debris, against a broader range of Listeria than PlyPSA, which showed little lytic activity toward Listeria strains not from serovar 4. Both endolysins were also capable of maintaining lytic activity to varying extents at refrigeration temperature. The effect of salt concentration and pH differed between PlyP40 and PlyPSA. Furthermore, we added the endolysins to QF and monitored their ability to control L. monocytogenes contamination over 28 d of cold storage. Both PlyP40 and PlyPSA were capable of lowering QF inoculum cell counts compared with the control; however, both were less effective than the previously characterized PlyP100. Further characterization of endolysins will continue to open opportunities to optimization and implementation in a variety of food matrices for controlling pathogen contamination.